Outcomes associated with higher relational continuity in the treatment of persons with asthma or chronic obstructive pulmonary disease: A systematic review. (July 2022) - Lytsy, Per; Engström, Sven; Ekstedt, Mirjam; Engström, Ingemar; Hansson, Lars; Ali, Lilas; Fredriksson, Maja Kärrman; Liliemark, Jan; Berg, Jenny
Summary: Background: Asthma and chronic obstructive pulmonary disease (COPD) are chronic conditions where relational continuity of care, as in regularly meeting the same health care provider, creates opportunities for monitoring and adjustment of treatment based on an individual's changing needs, potentially affecting quality of delivered care. The aim of this systematic review was to investigate the effects of relational continuity in the treatment of persons with asthma or COPD. Methods: Eleven databases (CINAHL, Medline, PsycINFO, Scopus, Embase, Cochrane Library, Database of Systematic Review of Effects, DARE, Epistemonikos, NICE Evidence Search, KSR Evidence and AHRQ) were searched between January 1, 2000, and February 1 - 4, 2021, for controlled and observational studies about relational continuity and health outcomes for persons with asthma and/or COPD. Inclusion criteria were studies investigating an index or aspect relevant to relational continuity between a health professional/team of health professionals and patients. After screening, and assessment of study relevance and quality by at least two independent reviewers, studies with acceptable risk of bias were included and summary data was extracted from the publications. Main outcomes were mortality, morbidity (including health care utilization) and cost measures. Syntheses without metanalyses were performed due to considerable study heterogeneity. The certainty of the summarized result was assessed using GRADE (the Grading of Recommendations Assessment, Development and Evaluation). PROSPERO study registration number: CRD42020196518. Findings: We identified 2824 unique references and included 15 studies (14 observational and 1 randomized controlled trial) in the review, from which results were derived for six outcomes. For persons with asthma or COPD we found that higher compared to lower relational continuity of care prevents premature mortality (low certainty; 2 studies, 111 545 participants), lowers risk of emergency department visits (low certainty, 5 studies, 362 305 participates) and risk of hospitalization (moderate certainty, 9 studies, 525 716 participants), and lowers health care costs (low certainty; 4 studies, 390 682 participants). Results regarding treatment adherence (1 study, 971 participants) and patient perceptions (3 studies, 2026 participants) were assessed as having very low certainty. Interpretation: Low to moderate certainty evidence suggests that higher versus lower relational continuity of care for persons with asthma or COPD prevents premature mortality, lowers risks of unplanned health care utilization and reduces health care costs. The results may be of value when planning care for individuals and for policymakers in organizing health care and developing guidelines for treatment and follow-up routines. Funding: None.